2014
DOI: 10.1007/s10163-014-0302-6
|View full text |Cite
|
Sign up to set email alerts
|

Surface and porous characterization of activated carbon prepared from pyrolysis of biomass (rice straw) by two-stage procedure and its applications in supercapacitor electrodes

Abstract: In this study, we used a two-stage process and phosphoric acid to thermochemically transform waste biomass rice straw into porous carbon (PC) for the preparation of high-performance supercapacitor electrodes. The morphological and chemical characteristics of PC were investigated by X-ray diffraction, scanning electron microscopy, surface area, and porosity analyses by the BET (Brunauer, Emmett, and Teller) nitrogen adsorption method, Fourier transform infrared spectroscopy. The modification process leads to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 39 publications
(27 reference statements)
0
22
0
Order By: Relevance
“…Up to now, several works have been reported on preparing porous carbons from RS. 24,25 Unfortunately, none of them utilized the intrinsic silica as a self-biotemplate to develop N-self-doped HPCs. And thus, the supercapacitances and rate capacities or energy densities of the as-prepared porous carbons are moderate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Up to now, several works have been reported on preparing porous carbons from RS. 24,25 Unfortunately, none of them utilized the intrinsic silica as a self-biotemplate to develop N-self-doped HPCs. And thus, the supercapacitances and rate capacities or energy densities of the as-prepared porous carbons are moderate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This indicates that the highest sample density reduction was found at GX-via activation of 35.86% confirming the high porosity nature which is dominated by various pore structures. This property is very much needed for the basic electrode material as a supercapacitor energy storage application [34]. From the density analysis of this monolith, it can be confirmed that the sample GXvia activation produces good material properties to improve their electrochemical properties in supercapacitor applications [35].…”
Section: Figure 2 the Density Of Gx-non Activation And Gx-via Activationmentioning
confidence: 75%
“…At present, the main preparation methods of biomass-activated carbon include direct heating carbonization, hydrothermal carbonization and carbonization-activation. [25][26][27] The biomass-activated carbon prepared by direct thermal carbonization or hydrothermal carbonization has small specic surface area, small pore diameter and low capacitance, which are not suitable for the preparation of high-performance electrode materials for double-layer supercapacitors. However, the carbonization activation method of pre-carbonization and subsequent activation by adding an activator can effectively solve the problems.…”
Section: Introductionmentioning
confidence: 99%